Answer:
d=10 units
Explanation:
Hello.
Step 1
the formula of the distance between two points is based on the Pythagorean theorem, which states that in a rectangle :
![side^(2) +side^(2)=hypotenuse^(2)\\](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9jqjsx5qtj9ycu6c1ojdzhj8eubdrjxtxy.png)
Now, suppose we have two points P1(X1,Y1) and P2(X2,Y2), the distance between the two points will be the hypotenuse of our triangle, the difference in x will be the adjacent leg, and the difference in coordinates in y will be our opposite leg.
adjacent side =X2-X1
opposite side=Y2-Y1
hypotenuse=distance between P1 and P2
replacing
![adjacent\ leg^(2) +opposite\ leg^(2)=hypotenuse^(2)\\(x_(2)-x_(1)) ^(2) +(y_(2)-y_(1))^(2)=(distance between\ P1\ and\ P2)^(2)\\ distance between\ P1\ and\ P2=\sqrt{(x_(2)-x_(1)) ^(2) +(y_(2)-y_(1))^(2)} \\\\](https://img.qammunity.org/2019/formulas/mathematics/middle-school/pyt55ejolg57agj6gh14m7pwfye9d3clk3.png)
we take only the positive root because it is a distance, a negative distance makes no sense
Step 2
find the distance between A(1,1) and B (7,-7) using the formula
Let
P1=A(1,1)
P2=B(7,-7)
put the values into the formula
![d=\sqrt{(x_(2)-x_(1)) ^(2) +(y_(2)-y_(1))^(2)} \\let\\\\x_(1)=1,y_(1)=1,x_(2)=7,y_(2)=-7\\d=\sqrt{(7-1) ^(2) +(-7-(1))^(2)}\\d=\sqrt{(6) ^(2) +(-8)^(2)}\\d=√(36 +64)\\d=√(100)\\ d=10](https://img.qammunity.org/2019/formulas/mathematics/middle-school/yj3dwzno6f51u147tdm2rr03uvspvl31la.png)
d=10 units
Have a good day.